Community of material and mental culture of turks and Nothern American native people (Eurasian Journal of Philology Science and Education, 2015)
Parallel “prototukmen-Indean of North American” has engrossed the mind of scientists of different fields of science: from genetic to culture experts and fine art experts for about 100 years. Commonality of the material and mentalculture of turkomen and native people of Northern America is clear and based on the anthropogenetic relatives. Genetic relatives of turkomen and amerins’ conditionates cultural community which is preserved in mythopoetics and folklore as a non-material cultural heritage transmitted through the artistry. At this date the fact of genetic identity of paleo-Asian and partly Central Asia people with amerinds is described, studied and proved. Settlement of Americ was through now nonexistent Bereng vent and Bereng which was sink during last englacial melting world ocean in 10-15 thousandsyear century B.C.E.
Keywords: comparative analysis; ethnic community; culture; art; totem.